Nuevos movimientos eclesiales - Rodrigues, Luís Miguel Figueiredo (2013)
The new ecclesial movements have a particular focus in recent times in the Church, and have come to be known as the Spring of the Spirit. This article addresses this reality, their characteristics and their potential. It highlights the pastoral opportunity to live and profess the apostolic faith in an ever more authentic way.